1996
DOI: 10.1002/mrm.1910360503
|View full text |Cite
|
Sign up to set email alerts
|

Broadband decoupled, 1H‐localized 13C MRS of the human brain at 4 tesla

Abstract: Broadband proton decoupling of the entire 13C spectrum was possible within power absorption guidelines and resulted in the detection of narrow (as low as 2-3 Hz), natural abundance signals from metabolites such as myo-inositol, glutamate, N-acetyl-aspartate, and glutamine from 72 cm3 volumes in the human brain. To overcome the chemical shift displacement error, three-dimensional localization on the 1H z magnetization was combined with polarization transfer. Efficiency of the heteronuclear localization method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 26 publications
1
78
0
Order By: Relevance
“…Previous studies have reported the successful use of 1 H to 13 C polarization transfer in the human brain (23,24). However, these studies used localization techniques and were thus restricted to small regions.…”
Section: Fig 8 Natural Abundance In Vivomentioning
confidence: 99%
“…Previous studies have reported the successful use of 1 H to 13 C polarization transfer in the human brain (23,24). However, these studies used localization techniques and were thus restricted to small regions.…”
Section: Fig 8 Natural Abundance In Vivomentioning
confidence: 99%
“…In contrast, direct detection requires 1 H decoupling, i.e., high-frequency but narrowband decoupling (⌬ / ϳ 2 ppm). Both direct and indirect approaches are confronted to specific absorption rates approaching the FDA guidelines, even when quadrature half-volume coils are used for decoupling (8,11,25,30), as discussed by Adriany and Gruetter (11). In this regard, it is advantageous to perform indirect detection without decoupling using a 1 H PRESS sequence.…”
Section: Nmr Detection Of 13 C Label On Human Systemsmentioning
confidence: 99%
“…In principle, two strategies are available: isotope or magnetic labeling. Pulse chase or isotope labeling experiments 2,36 are beyond the scope of this review article, only spin labeling or spin transfer experiments will be covered. 10,37 Creatine kinase reaction…”
Section: In Vivo Applicationsmentioning
confidence: 99%